Educational Characteristics and Value Topeng Lengger Njambu Dance in Wonosobo District - Sofia Rachmawati; Muhammad Jazuli; Agus Cahyono (Jurnal Penelitian Pendidikan, 2023)
Lengger Mask Dance is a traditional art which is the identity of the people of Wonosobo Regency. The Lengger Mask Dance has a high appeal since 1910 until now. The existence of the Topeng Lengger dance which still exists has not been spared by its supporting community. There are two versions of the Lengger Mask Dance in Wonosobo Regency, namely the Njambu Lengger Mask Dance and the Njanti Lengger Mask Dance. Topeng Lengger Njambu is the first Topeng Lengger Dance that was born and became a patron for other Topeng Lengger Dances in Wonosobo Regency. The characteristics of the Lengger Njambu Mask Dance became the reason for the researchers to conduct this research, then the researchers examined the educational value contained in the Lengger Njambu Mask Dance performances. This research examines the Njambu Lengger Mask Dance from the characteristics and educational value of the Njambu Lengger Mask Dance in Wonosobo Regency. The approach in this study uses a descriptive qualitative method. Data and data sources obtained through primary data and secondary data. Data collection used observation, interviews and documentation studies. Validity technique using triangulation technique. Data analysis through data collection, reduction, presentation, and verification. Research results are as follows. The form of the Lengger Njambu Mask Dance Performance is a description of the characteristics of the Wonosobo people. The characteristics of the Wonosobo people are described through the movement, clothing, and accompaniment of the Lengger Njambu mask dance. This causes the form of the Lengger Njambu Mask Dance to remain original and not experience much change. Among the characteristics that appear in the form of the Lengger Njambu Mask Dance performance are upholding religious values, being polite, neat, and calm. In addition to describing the characteristics of the people of Wonosobo Regency, the Lengger Njambu Mask Dance also contains educational values such as religion, love for the motherland, and responsibility.